Penyuluhan Hukum Perkawinan Hindu Sebagai Strategi Menuju Desa Sadar Hukum - I Putu Gelgel; I Putu Sastra Wibawa (UNHI Press, 2018)
Legal awareness of Hindu marriage law that has not been maximal is a problem for the community in Tista Village, Busung Biu Subdistrict, Buleleng Regency. One of the strategies to increase the legal awareness of Tista Village community especially in understanding Hindu marriage law through legal education is done to achieve maximal legal awareness of the community. The Community Service Team succeeded in providing an understanding to the public about the importance of knowing the law of Hindu marriage. Hindu marriage counseling activities by combining lecture and case-case models can be a model of future counseling by no longer doing legal counseling with lecture models only.